DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE - Samadov Sevinchbek (Ecomind Press, 2025)
The article analyzes the application of big data technology in the economy and discusses issues related to its improvement. Statistical data and analytical reviews are used, drawing from scientific publications on the topic both in Uzbekistan and abroad. In addition, the main problems of using big data in the economy are highlighted.
Keywords: Big data, economy, information system, requirements, artificial intelligence, machine learning, database, automation, financial reporting.